Membangun Jiwa Kewirausahaan Peserta Didik Melalui Projek Penguatan Profil Pelajar Pancasila di SMAN 1 Gresik - Yuni Fitriah; Mufarrihul Hazin; Amrozi Khamidi; Mochamad Nursalim; Ayu Wulandari; Kaniati Amalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to determine how the implementation of the Pancasila Student Profile Strengthening Project (P5) can foster entrepreneurial spirit among students. The Pancasila Student Profile is a character education concept aimed at developing Indonesian students who practice the noble values of Pancasila. This research was conducted at SMAN 1 Gresik. This study uses a qualitative descriptive approach. In this study, data collection techniques were carried out through observation, interviews, and documentation. The research instruments used in this study include interview guidelines, observation sheets, and documentation guidelines. Data analysis technique uses Huberman's model with three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the Pancasila Student Profile Strengthening Project (P5) can build students' entrepreneurial spirit through creativity and innovation, collaboration and leadership, as well as social responsibility and ethics. The values of Pancasila instilled through the project provide a strong foundation for students to develop ethical and responsible entrepreneurship. The Pancasila Student Profile Strengthening Project has proven to provide meaningful learning experiences, thus preparing students to face the challenges of the real world. Keywords: Pancasila Student Profile Strengthening Project (P5), Entrepreneurship, Creativity, Innovation , Social Responsibility